World Cup “Brazil 2014”: the political-ideological use of soccer in government advertisements (Research, Society and Development, 2020)
The goal of the research was to analyze, through textual strategies, how the political-ideological use of football took place in advertisements of the federal government elaborated for the 2014 World Cup. For this, we used the guidelines of Textual Analysis based on Semiotics. The analysis showed that federal government used soccer for political-ideological purposes by reinforcing the feeling of patriotism, combating racism, the presence of intentions to promote acceptance of the World Cup in Brazil and, intertextual relations with the political platform of the Workers' Party, which at that time ruled the country and would run for reelection in 2014.